Action Based Community Development by STAI As-sunnah: Rebuilding Islamic Piobang in The Modern Era - Muhammad Fadhlan Is; Slamet Riyadi; Farouq Alfaritsi; Salmi Adrizal; Abdurahman Afif; Muhammad Dimas Suhaimi Zein; Tiy Kusmarrabbi Karo (ASSUNNAH PRESS, 2023)
Nagari Piobang is the hometown of Haji Piobang, one of the purization figures of Islam in Indonesia. As his homeland, the Piobang people should also inherit the spirit of Haji Piobang's struggle to uphold Islamic teachings. But in reality, people are no longer passionate about religious activities. This action research aims to revive the community's spirit of implementing Sharia in Nagari Piobang, West Sumatra. This research method is Action Based Community Development, which is action research that seeks to revive the spirit of the community by bringing up the glory of its characters in the past. Through this action research, it is hoped that it can regenerate the spirit of the community to uphold sustainable Islamic law with positive activities for the young generation of Piobang. Several programs are designed to spark public interest in religious activities, including Tahfiz Quran and Tahsin. Both of these programs are very popular, considering that this kind of activity has been absent in the community for a long time. The program's sustainability is also guaranteed by special funds from the community, amounting to approximately 30 million, for the fulfillment of infrastructure facilities. The Action Based Community Development activity carried out during Ramadan 1444 H was very satisfying. All success standards designed at the beginning of the activity are achieved with indicators that exceed expectations. Although it had dimmed, it turned out that the spirit of Hajj Piobang did not die in the Nagari Piobang, West Sumatra community. This is evidenced by the revival of religious programs for the younger generation with a form more following the times.